Intimacy : the shared part of me - Molina, Maria Elisa (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"The concept of intimacy puts forth important challenges to contemporary cultural psychology. Intimacy refers to a felt experience of interiority that although is intuitively comprehensible, does not have rigorously defined limits. Intimacy can refer to a content, an object, a person, ownership, or even a part of one's own body. A potentially problematic issue for cultural psychology is that acknowledging intimacy seems to bound the Self to areas disjointed from the social sphere. In a globalized world, we witness a developmental process where social life becomes sectioned, where people are involved in an identity search by foregrounding certain social roles. With this backdrop in mind, people redefine and rebuild their intimacy spaces and the ways they roam from these to the public and collective realm. Exploring the current historical situation leads us to consider intimacy as culture in the making; certainly, in the way it manifests itself, but particularly in how we approach and understand it. The lived (experienced) dimension of intimacy becomes truly important, since it casts new light on what we mean by intimacy in different spheres of the self's life, as well as life with others"-- Provided by publisher.
Keywords: Intimacy (Psychology); Interpersonal relations.; Psychology -- Interpersonal Relations.; Social, group or collective psychology.; Interpersonal communication and skills.; Sociology: family and relationships.; elektronické knihy; electronic books